Attitudes towards and knowledge of nutrition support amongst health care professionals on London intensive care units. (24th August 2013) - Lane, C.; Wedlake, L. J.; Dougherty, L.; Shaw, C.
Abstract: Background: Nutrition support on intensive care units (ICUs) has gained a higher profile ever since the development of published guidelines ( Clin. Nutr . 2006, 25, 210; J. Parenter. Enteral Nutr . 2009, 33, 277;http://www.nice.org.uk/Guidance/CG32 ; Clin. Nutr . 2009, 28, 387). However, there are limited data available on knowledge and attitudes towards nutrition support specific to ICU. Methods: An online survey was sent to all healthcare professionals working on ICUs across London via an e‐mail link. The aim of the study was to assess the knowledge base of and attitudes of staff towards nutrition support, within an ICU setting, and to understand their educational needs. The results were analysed using descriptive statistics. Results: Attitudes were in line with the evidence in current nutrition guidelines. The proportion of healthcare professionals who were regarded as demonstrating sufficient understanding of the evidence set out in the nutrition support guidelines were 44% of clinicians, 26% of nurses, 76% of dietitians and 67% of other staff. In total, 59% of staff wanted more education on a number of aspects related to nutrition support on ICU. Conclusions: The present study highlights the need for more prominent dissemination of the current guidelines and illustrates the preferred mode. Specific gaps in knowledge regarding energy intake and the use of parenteral feeding are highlighted. It is hoped that the present survey will help to guide education in this area.